SISTEM DETEKSI GANGGUAN DEPRESI PADA ANAK-ANAK DAN REMAJA - Haryanto Haryanto; Hartati Dyah Wahyuni; Siti Nandiroh (Jurnal Ilmiah Teknik Industri, 2015)
Depression or mental stress is not happen to adults only. Children and adolescents may also experience depression. About 5 percent of children and adolescents in Indonesia suffer depression.  Depression prevalent in schools and in their families. Behavior change is a sign of depression, such as suddenly said he wanted to die or living alone. Early diagnosis and treatment are very important for children and adolescents depressed. Cognitive behavioral therapy (CBT) and interpersonal psychotherapy (IPT) are forms of individual therapy proven to be effective in treating depression, in addition to the use of antidepressant drugs. The author makes a system of early detection of depressive disorders in children and adolescents, to monitor children and adolescents suffer from depression or not. The system used in the early detection utilizing web technology and mobile phone. Monitoring and inputting existing symptoms in children and adolescents is done through a test of depression. Test depression then processed and entered into a database. Test results will indicate the degree of depression based on the scores. With that score, the degree of depressed children and adolescents monitored can be concluded.